Revisiting the binding designation between source and target domains in the creation of Javanese food names metaphors - Hendrokumoro; I Dewa Putu Wijana; Nadia Khumairo Ma’shumah (Cogent Arts & Humanities, 2023)
This study aims to investigate metaphorical representation in Javanese food names in terms of linguistic forms, metaphorical element distribution, similarity basis, source domains, and sociocultural factors underlying their existence. This study employed a qualitative approach by positioning researchers for collecting and generating data through literature studies, with questionnaire responses from 50 native respondents. The results of the analysis showed that Javanese metaphorical food names were expressed in various linguistic forms, including monomorphemic and compounded words consisting of compounding (whether on the first, last, or entire expression), contraction, and reduplication processes. Further analysis then revealed that everything related to humans and mythologies, animals, plants, natures, things, and actions were used as metaphor source domains; and compared based on shape, size, function, texture, colour, taste, and state. By considering the juxtaposition between metaphor and culture, this study concluded that the environment significantly impacts the meanings that Javanese members of groups use to understand other aspects of their world.